A Spatial Epidemiological Investigation of COVID-19 in the MENA Region: Modeling Incidence and Impact Factors - Mustafa Shebani Aboalyem; Mohd Tahir Ismail (Malaysian Journal of Science, 2024)
The COVID-19 pandemic has negatively impacted the global economy and society. World Health Organization (WHO) reported that as of early July 2023, the virus has infected more than 690 million individuals and has resulted in more than 6.9 million deaths worldwide. This study aims to investigate spatial epidemiological factors of COVID-19 in the Middle East and North Africa (MENA) region. By employing various spatial modeling techniques, this study establishes that multiscale geographically weighted regression (MGWR) is the best-fitted model, with the lowest residual sum of squares (11.22) and the lowest Akaike’s Information Criteria (AIC) value (58.41), explaining 84.3% of the variance (R2=0.843). Our study finds that population density, total vaccination doses, unemployment, and GDP per capita are critical factors associated with COVID-19 in the MENA region. These valuable insights provide policymakers and public healthcare experts with the information needed to develop targeted interventions that can mitigate risk factors related to the COVID-19 pandemic.